2009
DOI: 10.1016/j.bone.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 mediates HDAC-dependent transcriptional repression of osteocalcin expression during osteoblast differentiation

Abstract: We previously reported that the in vivo and in vitro suppression of Nuclear Factor of Activated T Cells (NFAT) signaling increases osteoblast differentiation and bone formation. To investigate the mechanism by which NFATc1 regulates osteoblast differentiation, we established an osteoblast cell line that overexpresses a constitutively active NFATc1 (ca-NFATc1). The activation of NFATc1 significantly inhibits osteoblast differentiation and function, demonstrated by inhibition of alkaline phosphatase activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 46 publications
6
89
2
Order By: Relevance
“…Indeed, although NFAT is an important mediator for the expression of various cytokines, evidence has accumulated that NFAT also represses the transcription of some genes. NFATc1 and NFATc2 repress the expression of osteocalcin and Cdk4, respectively, by increased recruitment of histone deacetylase (39,40). Thus, NFAT1 may inhibit CCR9 expression by recruiting histone deacetylase to the Ccr9 promoter or by preventing the complex formation of NFATc2 with RARa/RXRa and other transcriptional factors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although NFAT is an important mediator for the expression of various cytokines, evidence has accumulated that NFAT also represses the transcription of some genes. NFATc1 and NFATc2 repress the expression of osteocalcin and Cdk4, respectively, by increased recruitment of histone deacetylase (39,40). Thus, NFAT1 may inhibit CCR9 expression by recruiting histone deacetylase to the Ccr9 promoter or by preventing the complex formation of NFATc2 with RARa/RXRa and other transcriptional factors.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NFATc1 has been previously shown to significantly inhibit osteoblast differentiation and activity via repression of osteocalcin. [76]. Thus HDACi that suppress NFATc1 may be able to both inhibit bone resorption and enhance osteoblast bone formation.…”
Section: General Effects Of Hdaci On Bone Formationmentioning
confidence: 99%
“…These results suggest that the involvement of calcineurin-NFAT pathway is likely much more complex in osteoblasts with different isoform and possibly different NFAT protein exerting distinct function. In a separate study by the same lab, it was found that NFATc1 suppressed the promoter of osteocalcin during osteoblast differentiation possibly through a HDAC mediated mechanism [73]. Histone deacetylase (HDAC) 3 has been shown to interact with the amino terminus of Runx2 to repress osteocalcin promoter and osteoblast maturation [74].…”
Section: Role Of Calcineurin In Osteoblast Regulationmentioning
confidence: 99%
“…This is fascinating and demonstrates that the skeletal system and the endocrine system reciprocally regulate each other. Since NFATc1 regulates the promoter of osteocalcin [70,73,79], one may suspect whether or not NFATc1 may also play an indirect role in regulating testosterone level and impacting bone health in males.…”
Section: Regulation Of Nfatc1 and Osteoblasts By Reproductive Hormonesmentioning
confidence: 99%